Plantain (Plantago lanceolata L.) as a natural mitigation strategy to reduce nitrogen losses from pasture-based dairy systems : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Agricultural Sciences at Massey University, Manawatu, New Zealand - Rodríguez Gelós, Maria Jimena (Massey University, 2020)
The incorporation of plantain (Plantago lanceolata) into cows’ diet can reduce urine nitrogen (N) concentrations and modify the soil N cycle in urine patches by inhibiting nitrification. The objective of this thesis was to assess the potential of plantain as a mitigation option for N loss from dairy farms to the environment by measuring N leaching (nitrate [ NO₃⁻]), and N emissions (nitrous oxide [N₂O] and ammonia [NO₃⁻]) from plantain swards on a Pallic soil, and to evaluate the inhibitor effect of aucubin, a secondary metabolite, on N losses from soil. An important aspect of this study was the evaluation of NO₃⁻ leaching at the paddock scale from three pasture treatments (plantain, plantain-clovers mix and ryegrass-white clover) throughout two grazing seasons. Pasture treatments were grazed with lactating cows approximately monthly from September 2017 to May 2019. All the drainage from the grazed plots was monitored and sampled for NO₃⁻ and total N analyses during the 2017, 2018 and 2019 drainage seasons. The effect of plantain on N₂O and NH₃ emissions was evaluated in two field experiments carried out in spring 2017 and autumn/winter 2018. The N₂O emissions from soil were measured using the static chamber method, and NH₃ losses with the dynamic chamber method. In this field experiment the effects of adding two urine types (from cows grazing plantain or ryegrass-white clover) to two swards (plantain or ryegrass-white clover) were evaluated. The ability of aucubin to reduce N losses from urine patches was studied in a lysimeter experiment where aucubin was applied along with urine from cows grazing ryegrass-white clover pasture to ryegrass-white clover and plantain swards. In a hydroponic experiment, the release of secondary metabolites from a plantain root system was quantified. The plantain pasture treatment reduced NO₃⁻ leaching by 48 and 58% (2.6 and 3.8 kg NO₃⁻-N ha⁻¹, respectively) compared to ryegrass-white clover and plantain-clovers mix pasture treatments, in the 2018 drainage season. During the 2019 drainage season, NO₃⁻ leaching between the plantain (4.0 kg NO₃⁻-N ha⁻¹) and ryegrass-white clover (3.1 kg NO₃⁻-N ha⁻¹) treatments were similar, which was likely due to a lower proportion of plantain in the sward during the critical summer-autumn period. In spring 2017, even though the urea-N concentration was 45% lower in urine of cows fed plantain than in urine of cows fed ryegrass-white clover swards, the cumulative N₂O emissions from urine of cows grazing plantain was similar to urine of cows grazing ryegrass-white clover swards. Nitrous oxide emissions were reduced 31% by the plantain sward (1.4 kg N₂O-N ha⁻¹) in spring 2017. In autumn/winter 2018, N₂O emissions from urine of cows grazing plantain (urea-N concentration was 40% lower in the urine of cows fed plantain than in the urine of cows grazing ryegrass-white clover pastures) were 48% lower (4.3 kg N₂O-N ha⁻¹) than from urine of cows grazing ryegrass-white clover. However, in this season, the cumulative N₂O losses were 69% (7.1 kg N₂O-N ha⁻¹) higher from the plantain sward than the ryegrass-white clover sward and were associated with an increase in the water filled pore space (WFPS) in the plantain soil. The lower urea-N concentration in urine from cows fed plantain compared to ryegrass-white clover reduced NH₃ losses from plantain and ryegrass-white clover swards in both spring 2017 and in autumn/winter 2018. The lysimeter experiment also showed that plantain swards reduced N₂O emissions by 50% (9.0 kg N₂O-N ha⁻¹) compared to ryegrass-white clover swards. The addition of aucubin reduced the N₂O emissions from urine patches by 36% in ryegrass-white clover swards. Only small concentrations of secondary metabolites were detected in the roots exudates of plantain plants grown in the hydroponic experiment. A high aucubin concentration (12 g kg⁻¹ DM) in plantain leaves was observed after 50 and 60 days of the hydroponic study. In conclusion, this research demonstrates the potential of plantain to mitigate N leaching from pastoral dairy systems and N₂O and NH₃ emissions from urine patches by reducing the N and urea-N concentrations in cow urine. There was also evidence of a plantain sward effect on N dynamics in the soil, which decreased N₂O emissions, possibly through the release of aucubin into the soil via leaf litter.
Keywords: Plantago; Dairy cattle; Feeding and feeds; Nitrification inhibitors; Dairy farming; Environmental aspects; New Zealand; 300210 Sustainable agricultural development; 300407 Crop and pasture nutrition